PERSPEKTIF KETERSEDIAAN GULA DOMESTIK DAN SWASEMBADA GULA NASIONAL Perspective of Domestic Sugar Availability and National Sugar Self-sufficiency - Yonas Hangga Saputra (Puslitbang Perkebunan, 2020)
This article aims at reviewing the perspective of domestic sugar availability and national sugar self-sufficiency. The review result shows that the existence of sugar as one of the basic needs of the Indonesian people is faced with a gap between production (2.5 million tons/year) and consumption (5.7 million tons/year), caused Indonesia has to import 3.2 million tons of sugar annually. During the last five years (2011-2015), the growth of sugar import (3.42%/year) was higher than those of consumption (3.19%/year), productivity (3.01%/year), and production (2.27%/year). In order to anticipate such conditions, the government has prepared a roadmap to increase production with a target of self-sufficiency in sugar. Therefore, it is required a comprehensive solution to solve sugar problems from cultivation aspect at upstreamlevel, processing aspect at midstream level, up to marketing aspect at downstream level. Coordination, participation, and cooperation among stakeholders are absolutely necessary while eliminating sectoral ego institutionally. It is purposed to support the availability of domestic sugar and the national sugar self-sufficiency.ABSTRAK Artikelini bertujuan mengulas perspektif ketersediaan gula domestik dan swasembada gula nasional Hasil ulasan menunjukkan bahwa keberadaan gula sebagai salah satu kebutuhan pokok masyarakat Indonesia berhadapan dengan kondisi kesenjangan antara produksi (2,5 juta ton/tahun) dengan konsumsi (5,7 juta ton/tahun), sehingga Indonesia harus mendatangkan gula impor sebesar 3,2 juta ton per tahun. Selama kurun waktu lima tahun terakhir (2011-2015), laju pertumbuhan impor gula (3,42%/tahun) lebih tinggi dari pada laju pertumbuhan konsumsi (3,19%/tahun), produktivitas (3,01%/tahun), dan produksi (2,27%/tahun). Dalam rangka mengantisipasi kondisi tersebut, pemerintah telah menyusun peta jalan peningkatan produksi dengan target swasembada gula. Untuk itu diperlukan solusi komprehensif dalam mengatasi permasalahan gula mulai dari aspek budidaya di bagian hulu, aspek pengolahan di bagian tengah, hingga aspek pemasaran di bagian hilir. Koordinasi, partisipasi, dan kerja sama antar pemangku kepentingan terkait mutlak diperlukan seraya menghilangkan ego sektoral pada masing-masing pihak. Tujuannya adalah dalam rangka mendukung ketersediaan gula domestik dan swasembada gula nasional.